2018
DOI: 10.1021/acsnano.8b07413
|View full text |Cite
|
Sign up to set email alerts
|

Three-Dimensional Integrated Ultra-Low-Volume Passive Microfluidics with Ion-Sensitive Field-Effect Transistors for Multiparameter Wearable Sweat Analyzers

Abstract: Wearable systems could offer noninvasive and real-time solutions for monitoring of biomarkers in human sweat as an alternative to blood testing. Recent studies have demonstrated that the concentration of certain biomarkers in sweat can be directly correlated to their concentrations in blood, making sweat a trusted biofluid candidate for noninvasive diagnostics. We introduce a fully on-chip integrated wearable sweat sensing system to track biochemical information at the surface of the skin in real time. This sy… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
79
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 79 publications
(81 citation statements)
references
References 43 publications
2
79
0
Order By: Relevance
“…This implementation of sweat measurement in this way can greatly miniaturize the size of the entire analysis sensor. Garcia‐Cordero et al combined the ISFET, which occupies only one square centimeter on the substrate, with microfluidic networks for multiplexed sweat electrolyte analysis (Figure c) . The results of real‐time measurements reveal that this ISFET exhibits high sensitivity and a linear response to the concentration of detected ions.…”
Section: Applications Of Wearable Microfluidic Sensorsmentioning
confidence: 99%
See 1 more Smart Citation
“…This implementation of sweat measurement in this way can greatly miniaturize the size of the entire analysis sensor. Garcia‐Cordero et al combined the ISFET, which occupies only one square centimeter on the substrate, with microfluidic networks for multiplexed sweat electrolyte analysis (Figure c) . The results of real‐time measurements reveal that this ISFET exhibits high sensitivity and a linear response to the concentration of detected ions.…”
Section: Applications Of Wearable Microfluidic Sensorsmentioning
confidence: 99%
“…c) Enlarged optical image of ISFET (left), illustration of microfluidic sweat sensor (middle), and results of real‐time potassium detection (right). Reproduced with permission . Copyright 2018, American Chemical Society.…”
Section: Applications Of Wearable Microfluidic Sensorsmentioning
confidence: 99%
“…Javey et al developed a spiral‐patterned microfluidic sensor and they demonstrated that the device can be used for dynamic sweat secretion analysis on sweat rate and the concentration of sweat constituents, such as pH, Na + , K + , Cl − , by simultaneously incorporating more sensing electrodes in the collection reservoir (Figure B). Similarly, some other groups also reported their multiparameter microfluidic wearable sweat analyzers to real‐time and continuous monitoring of sweat compositions.…”
Section: Physiological Signal Monitoring Of Microfluidics‐based Wearamentioning
confidence: 99%
“…[45,69] Microfluidic channels can obtain liquid samples using a combination of capillary force and action of the natural pressure (≈70 kPa) associated with perspiration. [45,[70][71][72][73][74][75] Toonder et al [70] designed and fabricated a sweat intake device by combining paper and a microfluidic channel in foil (Figure 1A). The paper absorbs sweat from skin surface when the device is attached to the skin, and then the microchannels and cavities in microfluidic foil will be filled with sweat by capillarity.…”
Section: Sample Collection Handling and Storagementioning
confidence: 99%
“…Nakata and colleagues developed the first ISFET to continuously monitor sweat pH and skin surface temperature, but it requires a large amount of exercise to collect sweat . Garcia‐Cordero uses a microfluidic channel to transport small amounts of sweat effectively, which enabled detection without a sweat sample . Although great improvements have been achieved by former researchers in the development of ISFET‐based sweat sensors, there still remain some problems, such as that soaking in sweat for a long time will cause degradation of the gate insulator, which makes it difficult to maintain stability during the long‐term testing of sweat, and the need to integrate reference electrodes for ISFET‐based wearable devices would make the design complicated .…”
Section: Introductionmentioning
confidence: 99%